Pengembangan bahan ajar geometri bermuatan keterampilan berpikir kritis berbasis model flipped learning - Yuliani, Aska Muta; Wasqita, Rachmat; Irham, Muhammad (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2025)
University students are required to possess critical thinking skills to face the challenges of the 21st century. However, preliminary observations of first-semester students in the Mathematics Education Program at STKIP Paracendekia NW Sumbawa indicate that their critical thinking skills remain low. To address this issue, the flipped learning model was implemented. This study aims to develop flipped learning-based teaching materials to foster students’ critical thinking skills. The research employs a development approach using the Four-D (4D) model, limited to the product validity testing stage. Data collection techniques include questionnaires, observations, interviews, and tests. The data were analyzed using descriptive qualitative and quantitative methods. The results show that the developed teaching materials include activities aligned with 12 critical thinking indicators and support independent learning. Validation by three experts indicated a validity level of 92.80%, categorized as highly valid. This module can be used in early-semester learning as a means to enhance students’ critical thinking skills and independent learning abilities.